Cardiopulmonary exercise testing in repaired tetralogy of Fallot: a valuable tool for pulmonary regurgitation severity assessment. (11th May 2021) - Garcia Bras, P; Sousa, L; Mano, T; Monteiro, A; Rito, T; Ilhao Moreira, R; Rio, P; Silva, S; Martins, C; Coito, S; Capile, E; Agapito, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction and purpose: The optimal timing for pulmonary valve replacement (PVR) in asymptomatic patients with repaired tetralogy of Fallot (TOF) and pulmonary regurgitation (PR) remains uncertain but is often guided by imaging characterization of the right ventricle. As cardiopulmonary exercise testing (CPET) performance is an accessible prognostic indicator, we assessed which CPET parameters best correlate with pulmonary regurgitation severity to potentially improve identification of high-risk patients. Methods: A retrospective chart review was done from 2009 to 2018 on adult patients with repaired TOF who underwent maximal effort cardiopulmonary exercise testing with cycle ergometry and with concurrent pulmonary function testing. Demographics, standard measures of CPET interpretation, and major cardiovascular outcomes were collected. Results: Cardiopulmonary exercise testing was performed in 54 adult repaired TOF patients (59% male), with a mean follow-up of 60 ± 33 months. The mean age was 34 ± 9 years. 30 patients (56%) had severe pulmonary regurgitation and 26 patients (48%) were submitted to PVR, with a 0% mortality rate. PVR was performed a mean 28 ± 7 years after TOF repair surgery. There was moderate to severe right ventricular dysfunction in 11 patients (20%). 12 patients (22%) had a hospitalization for heart failure. Arrhythmic events occurred in 9 patients (17%), mainly atrial fibrillation or atrial flutter (67%). 2 patients (4%) received an implantable cardioverter-defibrillator for secondary prevention of sudden cardiac death. Peak VO2 consumption (pVO2) showed no statistically significant correlation with severity of pulmonary regurgitation (HR 0.26, 95% CI 0.879-1.036, p= 0.262) or PVR (HR 0.92, 95% CI 0.829-1.028, p = 0.914), while percent of predicted pVO2 significantly correlated with severity of pulmonary regurgitation (HR 0.95, 95% CI 0.918-0.993, p = 0.020) and PVR (HR 0.94, 95% CI 0.886-0.992, p = 0.025). VE/VCO2 slope was not a significant predictor of severity of pulmonary regurgitation (HR 1.03, 95% CI 0.929-1.130, p = 0.622) or PVR (HR 1.04, 95% CI 0.952-1.128, p = 0.414) or) and neither cardiorespiratory optimal point (HR 0.94, 95% CI 0.786-1.120, p = 0.480) nor maximum end-tidal carbon dioxide pressure (PETCO2) (HR 0.93, 95% CI 0.846-1.037, p = 0.213) correlated with severity of pulmonary regurgitation or PVR. Conclusion: Percent of predicted peak VO2 had the highest predictive power of all CPET parameters analysed in adult repaired TOF patients. Preoperative CPET could be an accessible way to identify high-risk patients earlier for PVR and should therefore be included in the routine assessment of these patients.